2018
DOI: 10.1029/2018gl080527
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Rate of Electrostatic Dust Lofting Over Time on Airless Planetary Bodies

Abstract: We present the laboratory results on electrostatic dust lofting rates expected on airless planetary bodies. Dust lofting is shown to be a time‐dependent process that begins at a relatively fast rate on an initialized surface and slows down as time progresses. The slowdown is likely due to the filling of interparticle microcavities as a result of dust movement or the removal of loose upper layers, which reduces the microcavity charging effect. It is suggested that the transient dust lofting rate under the charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…One of prominent surface processes on airless bodies is electrostatic dust mobilization and transport, which has been related to a number of observations (Wang et al, , and references therein) and has been confirmed using laboratory experiments (Hood et al, ; Schwan et al, ; Wang et al, ) and computer simulations (Zimmerman et al, ). One of these space observations is the so‐called dust ponds, which are flat and smooth deposits of fine dust particles in the craters observed on both asteroid Eros (Robinson et al, ) and comet 67P (Thomas et al, ).…”
Section: Introductionmentioning
confidence: 72%
“…One of prominent surface processes on airless bodies is electrostatic dust mobilization and transport, which has been related to a number of observations (Wang et al, , and references therein) and has been confirmed using laboratory experiments (Hood et al, ; Schwan et al, ; Wang et al, ) and computer simulations (Zimmerman et al, ). One of these space observations is the so‐called dust ponds, which are flat and smooth deposits of fine dust particles in the craters observed on both asteroid Eros (Robinson et al, ) and comet 67P (Thomas et al, ).…”
Section: Introductionmentioning
confidence: 72%
“…The exact physical reasons for the absence of high concentrations of lunar dust particles over the sharp sunlight/shadow boundaries in CE‐3 landing site are not yet fully understood; however, the weak dust activity in the geologically young CE‐3 landing region (Yan et al, 2019) and the lack of strong electric field forces on the lunar surface for lunar dust particles to overcome gravity and cohesion (Popel et al, 2018; Szalay & Horányi, 2015; Wang et al, 2016) are the two most likely causes. However, it cannot be entirely ruled out that high concentrations of lunar dust particles may still exist in the lower lunar space environment at altitudes below ~2.05 m because recent laboratory experiments showed that the inner walls of microcavities between dust particles can collect very large negative charge under electron beam or UV radiation conditions (Hood et al, 2018; Schwan et al, 2017; Wang et al, 2016), and the negatively charged dust particles can be electrostatically lofted by the repulsion from the adjacent like‐charged particles to reach an equivalent height of ~0.11 m on the lunar surface, comparable to the height of the lunar horizon glow observed by Surveyors. Unfortunately, the SCP cannot detect dust particles at this height range.…”
Section: Resultsmentioning
confidence: 99%
“…If small particles are residing on the rocks by cohesion force, a supercharging effect near the terminator or the shadow on asteroids may free the particle from the AR with initial kinetic energy and achieve the condition H r a . From Wang et al (2016) (Figure 4 of them) and Hood et al (2018), particles of radius r a = 5−22 µm (2r a = 10−44 µm) could achieve an initial speed of up to v z,0 ∼ 0.6 m/s due to the supercharging effect at r h = 1 au. This is the aftermath of Coulomb interaction, and therefore the particle size range and initial speed are independent of asteroid size (D) or r h .…”
Section: Electrostatic Dust Lofting and Levitationmentioning
confidence: 96%
“…The electrostatic lofting mechanism, which is the mechanism that launches the particles from the AR, has recently been studied extensively both theoretically (Zimmerman et al 2016 experimentally (Wang et al 2016;Hood et al 2018). If small particles are residing on the rocks by cohesion force, a supercharging effect near the terminator or the shadow on asteroids may free the particle from the AR with initial kinetic energy and achieve the condition H r a .…”
Section: Electrostatic Dust Lofting and Levitationmentioning
confidence: 99%